The Relationship between Demographic Characteristic and Quality of Life in Patients with Coronary Artery Disease - Teguh Santoso; Suhartini Ismail; Untung Sujianto; Dwi Susilawati (NurseLine Journal, 2020)
Background: coronary artery disease is one of non-communicable disease that leading cause of death in the global, which can disturb physical, psychological, and social aspects on the quality of life (QoL). The perception of QoL are difference among patients. The purpose of this study was to examine the relationship between demographic characteristics and quality of life in patients with coronary artery disease. Methods: This is a cross-sectional study surveyed patients with coronary artery disease. Participants were 124 (96 males and 28 females) with purposive sampling. Quality of life was measured with (SF-36) questionnaire. Spearman rho correlation coefficient were used to examine the relationships between the independent and dependent variable. Results: Spearman rho correlation coefficient analysis indicated that demographic characteristics (age, gender, marital status, and alcohol consumption) were not correlated significantly, but education level, occupation, income, and exercise were correlated significantly with quality of life. Conclusion: There were statistically significant the relationship between demographic characteristics and quality of life in patients with coronary artery disease.